2007
DOI: 10.1523/jneurosci.5528-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Modulation of Plasticity of the Auditory Cortex Elicited by Fear Conditioning

Abstract: In the awake big brown bat, 30 min auditory fear conditioning elicits conditioned heart rate decrease and long-term best frequency (BF) shifts of cortical auditory neurons toward the frequency of the conditioned tone; 15 min conditioning elicits subthreshold cortical BF shifts that can be augmented by acetylcholine. The fear conditioning causes stress and an increase in the cortical serotonin (5-HT) level. Serotonergic neurons in the raphe nuclei associated with stress and fear project to the cerebral cortex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 60 publications
1
39
1
Order By: Relevance
“…These findings suggest that the serotonergic system is able to draw on information about both internal state and behavioral context in order to influence auditory processing on a time scale matched to behavior. Given that the serotonergic system is known to modulate auditory processing, it is an excellent system in which to measure the neurochemical mediation of context on sensory processing (Ebert and Ostwald, 1992;Hurley et al, 2002;Hurley and Pollak, 2005;Ji and Suga, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…These findings suggest that the serotonergic system is able to draw on information about both internal state and behavioral context in order to influence auditory processing on a time scale matched to behavior. Given that the serotonergic system is known to modulate auditory processing, it is an excellent system in which to measure the neurochemical mediation of context on sensory processing (Ebert and Ostwald, 1992;Hurley et al, 2002;Hurley and Pollak, 2005;Ji and Suga, 2007).…”
Section: Research Articlementioning
confidence: 99%
“…In particular, stressrelated behavioural arousal and vigilance are known to be modulated by a serotonergic system in mammals (Amat et al, 1998b;Amat et al, 1998c). Serotonin is thought to be involved in the process of memory consolidation following one-trial avoidance and fear conditioning which often elicits an increase in anxiety (Inoue et al, 1993;Inoue et al, 1994;Izquierdo et al, 2006;Ji and Suga, 2007;Ogren et al, 2008). Studies investigating the effect of stress on longterm potentiation (LTP) have also indicated that a serotonergic system has a variety of modulatory effects on LTP depending on the learning events (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are six hierarchical information processing levels in the central auditory system. The highest level is the auditory cortex where the learned or experienced sounds are registered (Edeline et al, 1993;Recanzone et al, 1993;Bakin and Weinberger, 1996;Pantev et al, 1998;Zhang et al, 2001Zhang et al, , 2006Ma and Suga, 2003;Polley et al, 2006;Alain et al, 2007;Froemke et al, 2007;Ji and Suga, 2007). The lowest level is the cochlear nucleus (CN) that gates all incoming signals from the ear to the brain (Kiang et al, 1967;Evans, 1975;Liberman and Kiang, 1978;Feng and Vater, 1985;Taberner and Liberman, 2005).…”
Section: Introductionmentioning
confidence: 99%